OTENTISITAS SUNNAH DAN KEDUDUKANNYA DALAM LEGISLASI HUKUM ISLAM - Hauqola, Nur Kholis (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2014)
This paper aims to discover the truth of the authenticity of the Sunnah as the basis of Islamic law legislation. The problem lies on the